PENGEMBANGAN ‘BOARDGAME SPOTLIGHT 9 KATA KUNCI MODERASI BERAGAMA’ SEBAGAI MEDIA PEMBELAJARAN DAN PENGUATAN KOMUNITAS PEMUDA LINTAS IMAN - Mariatul Asiah; Riza Saputra (As-Sidanah, 2026)
This Community Service (Pengabdian kepada Masyarakat) activity addresses the superficial understanding of religious moderation among an inter-faith youth community in South Kalimantan, where traditional dialogue methods proved rigid and ineffective for the deep internalisation of values. The project's main objective was to develop an innovative educational board game named "Spotlight" to serve as an effective learning medium for internalizing these values. The game explicitly integrates the Ministry of Religious Affairs' Nine Key Words of Religious Moderation, focusing on Humanity, Justice, Balance, Tolerance, and Anti-Violence. The methodology employed a service learning approach combined with participatory training and mentoring. The youth were actively involved from design and content development to field playtesting. The results demonstrate that the Spotlight Boardgame was successfully implemented and proved effective as 'edutainment.' It created a fun, equitable, and open learning atmosphere, significantly enhancing participants' comprehension of moderation concepts through interactive case simulations and reflective challenge cards. Furthermore, the game positively strengthened social networks among inter-faith communities, acting as a medium for social transformation that reinforces national, humanitarian, and tolerance values. The game has high potential for replication.